Peran Islam dalam Pengembangan Manajemen Pendidikan di Era Modern - Muh. Thoriq Aziz Kusuma; Supriyanto Supriyanto (Departement of Mathematics Education, 2023)
This journal looks at how Islamic education management shapes society and educational institutions. This research uses a qualitative-descriptive approach, conducts a literature study, and utilizes 3M, or recording, analyzing, and critiquing, as a data collection method. According to the findings, Islamic education management can play various roles in educational institutions, including curriculum management, student recruitment, personnel management, infrastructure and facilities management, administrative management, financial management, and public relations. In addition, professional researchers who have contributed to producing works that can build the nation through education, and have knowledge of management and leadership in becoming educational consultants, demonstrate the role of management in community development. In addition, the learning method used by educators to instill the value of tolerance in each student to address the diversity that exists in the community is an example of the role of management in community development.